Utility of Clinical Risk Index for Babies (CRIB-II) Scoring System in Prediction of Mortality in Premature Babies Admitted at Neonatal Intensive Care Unit, Combined Military Hospital (CMH), Rawalpindi - Awan, Haider Ali; Chaudhry, Shakeel Ahmed; Zia, Yusra; Tariq, Andleeb; Mujeeb, Namrah Fatima; Mir, Huma (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the predictive accuracy of the Clinical Risk Index for Babies (CRIB-II) scoring system for mortality in pre-mature babies admitted in neonatal intensive care unit. Study Design: Quasi-experimental. Place and Duration of Study: Department of Pediatrics, Combined Military Hospital, Rawalpindi, Pakistan, from Jan to Jun 2023. Methodology: A total of 280 neonates were assessed for CRIB-II score and predictive mortality. The CRIB-II score was assessed for all participants in the first 30 minutes of admission to NICU which included gender, gestational age, birth weight in grams on an electronic neonatal weight scale and base excess calculated by arterial blood gas analysis in addition to checking rectal temperature. Higher scores were hypothesized to associated with increased mortality. Results: After analyzing the primary variables, median CRIB-II scores between both groups showed values of 15.00 (IQR=3.50) in Group N versus 8.00 (IQR=2.00) in Group S (p<0.001). ROC (Receiver operative characteristics) and AUC (area under the curve) analysis showed AUC was 0.962 (95% CI=0.933-0.990) with the best suitable cut-off for sensitivity and specificity at CRIB-II score of 7.5 consistent with a 98.8% sensitivity and 72.3% specificity for mortality. Conclusion: CRIB-II is an effective scoring system for predicting mortality in NICUs for delivery of effective care.